Diseño de un pabellón arquitectónico efímero para el espacio público como escenario de actividades urbanas (2023)
In the city of Bucaramanga and its metropolitan area there is a high demand for social activities, cultural and neighborhood events, these events have become centralized and accessible to a part of the population, also the lack of public spaces and adequate equipment limits the participation of the communities located in the neighborhoods and peripheral areas. The ephemeral architecture is proposed as an innovative solution achieving the adaptation to different spaces and areas of occupation for the development of a pavilion from a modular structure that offers a creative and temporary solution to the lack of appropriate public spaces.